Efektifitas Kombinasi Teknik Marmet Dan Pijat Oksitosin terhadap Produksi Asi Ibu Post Seksio di Rumah Sakit Wilayah Jawa Tengah - Mardiyaningsih, Eko; Setyowati,; Sabri, Luknis (Jurusan Keperawatan FIKES UNSOED, 2011)
The research background was the deflation of breast-milk production during the first day after bearing. The objective of this research was to perceive the effectiveness of combination of marmet techniques and oxytocin massage to breast-milk production on post cesarean section women. This was an quasi experiment research using post test only design with a control group. Samples were collected with non-probability sampling techniques which was consecutive sampling, involving 54 total samples. Research result shows there is a difference between the proportion of breast milk production smoothness among controlled group and intervention group (p value=0.000). This study also shows that post cesarean section women given combination of marmet technique and oxytocin massage have 11.5 greater opportunity to have smooth breast-milk production compared to controlled group (OR= 11.500).